The effectiveness of using network modeling and simulation tools in evaluating students' performance / Mohd Faisal Ibrahim, Rozita Yunos and Nor Azimah Khalid - Ibrahim, Mohd Faisal; Yunos, Rozita; Khalid, Nor Azimah (2006)
The challenge in our education today is to identify the learning process and methodologies that can help students grasp the importance of knowledge and understand the way to apply that knowledge in the real world environment. Therefore, computer-simulation has been considered as a potential approach and methodology to achieve that objective. Based on Kirkpatrisk's model, the data is gathered through three types of questionnaires which are designed for three different levels of evaluations (students' reactions, behavioural changes and self-evaluation level) and two pre-test post-test to determines the level of student's knowledge and skills. The results of this study showed that most of the students increased their knowledge and skills performance after the use of computer-simulation in learning network design. Students of different gender, who are also with various academic backgrounds, as well working experiences, have unexpectedly produced high results on their questionnaires reports of students' reactions, behaviour changes and self-evaluations, where most of the results are in the positive level. The response given indicates that they have agreed towards the use of computer-simulation in learning network design because of the effectiveness of its usage. In conclusion, this learning process and methodology have a strong potential to increase the achievement of students' knowledge and skills, as needed in the real job market.